Análise fitoquímica, bromatológica, genotóxica e antimicrobiana de tubérculos de Tropaeolum pentaphyllum LAM - Cruz, Ritiel Corrêa da (2016)
Tropaeolum pentaphyllum Lam., belonging to Tropaeolaceae family, possess tubers commonly known as ‘’crem’’, popularly used in South of Brazil to the treatment of dermatosis and as spice. In order to verify its properties and popular applications, a phytochemistry and proximate analysis were made, as well as an evaluation of its antimicrobial and genotoxic potential. The quantification of macronutrients and mineral composition was executed according to international analytical guidelines, with fresh material. Also from fresh material, an essential oil extraction was made through hydrodistillation (Clevenger), lately submitted to gas chromatography-mass spectrometry (GC-MS) analysis and antimicrobial activity evaluation. From dried material, a crude hydroalcoholic extract (70%) was obtained, which through liquid-liquid partition generated the chloroform, ethyl acetate and n-butanol fractions, that along with the extract were submitted to total polyphenolics quantification (Folin-Ciocalteau), in vitro antioxidant capacity (DPPH) and polyphenolic compounds investigation by HPLC-DAD, as well as the biological activity tests. Antimicrobial activity was performed by broth microdilution, against a wide range of Gram-positive and negative bacteria, and yeasts and filamentous fungi, to obtain the inhibitory, bactericidal and fungicidal minimal concentrations. The genotoxicity was tested with culture of peripheral blood mononuclear cells isolated from blood, the evaluated genotoxic parameters were cell counting (Neubauer chamber), cell viability (Trypan blue), micronuclei formation (Giemsa) and DNA damage (Comet assay). Proximate and mineral analysis revealed that the main macronutrients of the tubers are water (69.73%) and carbohydrates (26.06%), the major mineral components are potassium, magnesium and calcium (450.05, 79.36 and 56.88 mg/100g of dry mass, respectively). GC-MS analysis revealed that the major constituent of the essential oil is benzyl isothiocyanate (BITC) (98.51%), and that the chloroform fraction is constituted by BITC, amides structurally related to it, fatty acids and its esters, elemental sulfur and a phytosterol. No flavonoid or phenolic acid were found through HPLC-DAD, which is in accordance with the low amount of total polyphenols and reduced antioxidant capacity. The essential oil and the chloroform fraction presented strong antimicrobial activity, with minimal inhibitory concentration values under 200 μg/mL, which is related to the presence of BITC, fatty acids and sulfur. The chloroform fraction and the crude extract presented genotoxic effects, possibly due to the presence of BITC and palmitic acid. The results presented a quantification of the major nutrients from the tubers, revealed the secondary metabolite responsible for its organoleptic properties and use as spice, demonstrated its antimicrobial activity, related to the traditional medicinal use, and revealed genotoxicity at the tested conditions.